The Relationship Between Women's Intention to Request a Labor Epidural Analgesia, Actually Delivering With Labor Epidural Analgesia, and Postpartum Depression at 6 Weeks: A Prospective Observational Study. (May 2018) - Orbach-Zinger, Sharon; Landau, Ruth; Harousch, Avi Ben; Ovad, Oren; Caspi, Liron; Kornilov, Evgeniya; Ioscovich, Alexander; Bracco, Danielle; Davis, Atara; Fireman, Shlomo; Hoshen, Moshe; Eidelman, Leonid A.
Abstract : BACKGROUND: Postpartum depression (PPD) is associated with pain during and after delivery, with studies showing reduced rates among women delivering with labor epidural analgesia (LEA). We hypothesized that women who intend to deliver with LEA but do not receive it are at higher risk for PPD at 6 weeks due to the combined experience of untreated labor pain and unmatched expectations during labor, and evaluated the interaction between labor plans related to LEA, satisfaction with pain control when actually delivering with LEA, and PPD at 6 weeks after delivery. METHODS: A total of 1497 women with a vaginal delivery were enrolled into this prospective longitudinal study. Women's initial intention to deliver with or without LEA, how they subsequently delivered, and satisfaction with pain relief were recorded on postpartum day 1. Primary aim was selected as PPD at 6 weeks among women intending to deliver with but subsequently delivering without LEA compared with the rest of the cohort. Primary outcome was PPD at 6 weeks using the Edinburgh Postnatal Depression Scale; PPD was defined with a score ≥10 (scale from 0 to 30). Demographic and obstetric data were recorded. Fisher exact test was used for comparisons between groups. The interaction between intention and actual delivery with regard to LEA and PPD was tested. RESULTS: Overall, 87 of 1326 women completing the study at 6 weeks had PPD (6.6%). For the primary aim, 439 (29.3%) delivered without LEA, of which 193 (12.9%) had intended to deliver with LEA; the PPD rate among these women was 8.1%, which was not statistically different from the rest of the cohort (6.3%; odds ratio [OR], 1.30; 95% confidence interval [CI], 0.72–2.38; P = .41). A total of 1058 women (70.7%) delivered with LEA and 439 (29.3%) delivered without; therefore, 1169 (78.1%) delivered as intended and 328 (21.9%) did not (unmatched expectations). Evaluating the interaction between effects, there was a strong negative additive interaction between intending to deliver without LEA and actually delivering with LEA (risk difference = −8.6%, 95% CI, 16.2%–1.6%; P = .014) suggesting that unmatched intention effect is significantly associated with negative outcome. In multiple regression analysis, while intending to deliver with LEA (OR, 1.06; 95% CI, 1.01–1.11; P = .029) and actually delivering with LEA (OR, 1.07; 95% CI, 1.01–1.13; P = .018) both increased the odds for PPD, the multiplicative interaction was protective (OR, 0.92; 95% CI, 0.86–0.99; P = .022), after adjusting for cofactors. CONCLUSIONS: Our study results did not demonstrate a significant increase in the odds for PPD at 6 weeks among women who intended to deliver with LEA but subsequently delivered without. However, we identified a protective interaction between intended LEA use and actual use on the incidence of PPD. Our data suggest an increased risk when women do not deliver as intended, particularly when not initially intending to deliver with LEA. The relationship between unplanned LEA and PPD may be mediated by a physically difficult delivery rather than or in addition to negative emotions related to unmet expectations or a sense of personal failure; therefore, counseling women after delivery to address any negative perceptions may be useful.